2019
DOI: 10.1016/j.aquaculture.2019.734269
|View full text |Cite
|
Sign up to set email alerts
|

Response to selection for increasing resistance to the spring mortality outbreaks in Mytilus edulis occurring in France since 2014

Abstract: Massive spring mortality outbreaks have been reported in Mytilus spp. in France since 2014. The main areas affected are the Pertuis Charentais Sounds and the coast of the Pays de la Loire, which cultivate mainly M. edulis, and the putative causal agents remain unknown. We report the results of the first generation of mass selection focused on survival and resistance to the spring mortality in M. edulis. Two stocks of mussels were sampled in the Pertuis Charentais Sounds in 2014; one of these went through a spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Results showed that a 'mortality window' opened in all sites during the spring season; similar observations also have been reported recently in France by other researchers (Benabdelmouna et al, 2018;Dégremont et al, 2019). This period corresponded to the spawning season of mussels.…”
Section: Temperature Conditioning and Mortalitysupporting
confidence: 88%
See 1 more Smart Citation
“…Results showed that a 'mortality window' opened in all sites during the spring season; similar observations also have been reported recently in France by other researchers (Benabdelmouna et al, 2018;Dégremont et al, 2019). This period corresponded to the spawning season of mussels.…”
Section: Temperature Conditioning and Mortalitysupporting
confidence: 88%
“…Similarly, Lokmer & Wegener (2015) argued that, in addition to the presence of pathogens, environmental factors have a strong impact on disease efficacy and mortality. In addition, it seems that genetics could also have an impact on mortality (Dickie et al, 1984;Mallet et al, 1987;Dégremont et al, 2019).…”
Section: Bacterial Profilesmentioning
confidence: 99%
“…Mallet and Haley (1984) indicated that mortality variation from one origin to another evidences the differences between populations of M. edulis; this is also what Dickie et al (1984) observed thanks to the significant differences in genetic constitution among the stock used in their experiments. Following this, Mallet et al (1986) showed that viability is highly heritable in M. edulis populations, and very recently, Dégremont, Maurouard, Rabiller, and Glize (2019) revealed that selected populations of French M. edulis were significantly more resistant to mortality outbreaks than natural unselected populations. Mytilus edulis and M. galloprovincialis are native species to the French coast, and numerous different natural populations exist and are capable to hybridize with each other.…”
Section: Mortality According To Original Spat Recruitment Sitementioning
confidence: 94%
“…Further experimental evidence for a genetic base comes from a selective breeding experiment of mussels for increasing resistance to the spring mortality. Progeny of survivors showed less mortality in the following outbreak, indicating a significant genetic improvement for the selected trait, while the putative agent remains still unknown (Dégremont et al 2019). We do not know the extent to which genetic factors affected the mortality outbreaks in the Oosterschelde.…”
Section: Genetic Effectsmentioning
confidence: 99%
“…MMEs can severely affect the commercial production of bivalve species and give rise to socio-economic vulnerabilities (Krause et al 2019). Since 2014, MMEs of blue mussel stocks have been reported on a nearly yearly basis from the west coast of France (Dégremont et al 2019). Mussels are an important aquaculture product in France and tools for reducing the economic consequence are limited (Avdelas et al 2021).…”
Section: Introductionmentioning
confidence: 99%